Pengaruh Model Pembelajaran TGT Pada Hasil Belajar Siswa Mata Pelajaran Akidah Akhlak di MA Al-Bairuny - Wardani, Dian Kusuma; Alaul Huda, Saihul Atho’; AL-Adawiyah, Robiatul Al (Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to determine the TGT learning model on the learning outcomes of class X students at MA Al-Bairuny Jombang. The method used is the experimental method. In this study, the research subjects were students of class X IPS I as an experimental class using the TGT learning model and class X IPS II as a control class using the lecture method. The data analysis technique used the